Design and Modeling of a Hundred Percent Renewable Energy Based Suburban Utility - Mathews, Shaji; Rajakaruna, Sumedha; Nayar, Chemmangot (IEEE, 2014)
This paper presents the complete system modelling, designing and controlling of an islanded minigrid power supply to the town of Carnarvon, Western Australia. Carnarvon power system is an isolated network supplying power to approximately5000 people via 205km of distribution lines. The existing power system is supplied by a number of large centralized 21MW Diesel Generators. The objective of this paper is to report the design, development and installation of a Photovoltaic (PV) diesel hybrid-power system such that the operating cost can be minimized and the load on the aging generators could be significantly reduced. The proposal includes the installation of two 25kW DC variable speed diesel generators and a suitably sized advanced battery bank at each suburban transformer to ensure hundred percent penetration of solar power by residential customers in the local area. This method of control is modelled and simulated in HOMER, PSpice and Matlab. The different modes of control used to integrate maximum solar energy, reduce diesel consumption and also the methodology imposed to store excess renewable energy for operation during the night.